Development and Characterization of Cross Arm for Power Transmission Line using Natural Fiber and Polymer - Begum S.; Fawzia S.; M Nainar M.A. (Elsevier, 2023)
Cross arms are the arm like equipment used in the power transmission line that holds the conductor with support of an insulator in a structure in power transmission line. Traditionally, transmission line structures have utilized treated lumber, steel, or concrete as a construction material. However, the difficulty in obtaining good quality timber and the shorter life span of non-quality timber wood have triggered the research to obtain alternate materials for cross arm. Hence, in this research project epoxy and thermoplastic elastomer were taken as polymer matrix and were reinforced with kenaf and oil palm fibers respectively. The percent of fibers was varied in the composite and were characterized by evaluating mechanical properties, water absorption, flammability, scanning electron micrographs (SEM) and energy dispersive X-ray (EDX). It was observed that the mechanical strength increased with increase of fiber content. However, water absorption was increased for both the composites. Fire resistance was observed for composite composed of TPE and oil palm fiber but kenaf fiber did not influence the epoxy composite in fire resistance. The SEM revealed good adherence of fiber in the matrix. Good interfacial bonding, fire resistance, suitable mechanical properties revealed that the natural fiber reinforced polymer composite can be considered as a suitable candidate for cross arm materials for power transmission lines in power generation. 2022 Elsevier Inc. All rights reserved.